The Role of Community in Malaria Vector Control - Solikhah Solikhah; Lina Handayani; Nooria Sukmaningtyas (International Journal of Public Health Science (IJPHS), 2013)
There are 40% (3 billion) of the world's population at risk of suffering from malaria with the addition of some 300-500 million cases and 1.5 to 1.7 million people died from suffering from malaria. In Indonesia to date, infectious disease, especially diseases that are transmitted by animals, especially insects, are still a public health problem. This study aimed to determine the role of the community in the prevention, control and eradication of malaria. This research was a qualitative study. Subjects of the study were public, community leaders, and health care providers. Data were analyzed by using content analysis and theory validation source. Community participation in malaria vector control through several ways to eradicate mosquito breeding, usage of mosquito nets, use of insect repellent, avoiding a night out and a survey of patients who return from leave. The community plays an active role in malaria vector control efforts by closing puddles, community service every week, and some people are already using nets.DOI: http://dx.doi.org/10.11591/ijphs.v2i4.5540